FINANCIAL PERFORMANCE AND CAPITAL STRUCTURE INFLUENCE ON COMPANY VALUE IN MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Chaerunnisa Rumianti; Ansir Launtu (Contemporary Journal on Business and Accounting, 2021)
Purpose – This study aims to test and analyze the effect of financial performance variables and capital structure on firm value in the food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange for the 2017 - 2019 period. Design/methodology/approach – This analysis method uses Multiple Linear Regression technique. Findings – The results of the study partially show that financial performance and capital structure have a negative and significant effect on firm value. Originality – The population is 26 manufacturing companies in the food and beverage sub-sector listed on the IDX for the period 2017-2019. Keywords: Capital Structure, Financial Performance, Firm Value Paper Type Research Result